The smartphone addiction tendency and quality of life in students with disabilities - Lavenia Lintin; Arthur Huwae (Psychology, Evaluation, and Technology in Educational Research, 2022)
This study aimed to determine the relationship between smartphone addiction and quality of life among students with disabilities. The method used was quantitative with a correlational design. The participants involved in this study were 33 students with disabilities chosen using snowball sampling. The research measurement used the Smartphone Addiction Scale (α = 0.943) and WHOQOL-BREF (α = 0.941). The results showed that there was no significant negative relationship between smartphone addiction and quality of life among students with disabilities (r = -0.238 and sig. = 0.091). These results indicate that the failure to achieve a quality of life for students with disabilities is not caused by smartphone addiction tendency. The use of smartphones can be controlled in a balanced way by students with disabilities in their daily activities so that it does not have a negative impact on their quality of life.